Divergent response of Pinus pumila growth to climate warming at different latitudes and in different simulation predictions - Yang, Jingwen; Zhang, Qiuliang; Song, Wenqi; An, Yang; Wang, Xiaochun (Frontiers in Forests and Global Change, 2022)
Understanding the responses of shrub growth to climate changes is key to accurately predicting the dynamic changes in the boreal forest ecosystem. A shrub-ring network based on 12 sites was established to explore the response of Pinus pumila growth to climate change in northeastern China. The sampling sites are distributed along the latitudinal gradient of 44.10° to 52.58° and were divided into three regions: south, central, and north. The results show that there have been significant differences in P. pumila growth trends at different latitudes in recent decades. From 1950 to 1980, P. pumila in the southern and central regions grew faster than in the northern region. From 1981 to 2014, however, the growth of P. pumila increased in the north but slowed in the south and central regions. The temperatures of the previous winter and current spring are the main factors limiting the growth of P. pumila in the north and south. In the central and southern regions, the growth of P. pumila is negatively correlated with precipitation of the previous and current summers. In the north, summer temperatures from 1981 to 2014 gradually inhibit the growth of P. pumila, while summer precipitation has a positive impact on growth. Our model indicates that the radial growth trend of P. pumila in the north is likely to decline as the climate warms. Surprisingly, the growth of P. pumila in the south is predicted to benefit from warming under the RCP4.5, RCP6.0, and RCP8.5 scenarios. Therefore, P. pumila may not expand northward in the context of climate warming.